2006
DOI: 10.1111/j.1744-313x.2006.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of non‐HLA genetic polymorphisms in graft‐versus‐host disease after haematopoietic stem cell transplantation

Abstract: Graft-versus-host disease (GvHD) is the main complication after haematopoietic stem cells transplantation (HSCT) and acute forms (aGvHD) occur in 20-40% of cases even after donor (D) and recipient (R) HLA matching, apparently because of D/R minor histocompatibility antigen (mHA) mismatches and cytokine polymorphisms. The genotype of cytokines and mHA of 77 haematological R following HSCT from HLA identical siblings were determined to detect genetic polymorphisms correlated with GvHD. We analysed TNFA (-863 C/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 32 publications
(49 reference statements)
2
23
0
3
Order By: Relevance
“…Other studies concerning IL-10 gene polymorphisms have shown conflicting results: some suggesting that a genotype relative to low production of IL-10 correlates with an increased risk of aGVHD 19,20 and others outlining an association between high producer genotype and acute or chronic GVHD. 7 In a large cohort of HLA-matched sibling transplants, the presence of the IL-10 ATA/ACC genotype in the recipient has been associated with a moderate risk of GVHD and lower risk of death in remission, 16 more severe GVHD occurring in groups without the IL-10 ATA haplotype.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies concerning IL-10 gene polymorphisms have shown conflicting results: some suggesting that a genotype relative to low production of IL-10 correlates with an increased risk of aGVHD 19,20 and others outlining an association between high producer genotype and acute or chronic GVHD. 7 In a large cohort of HLA-matched sibling transplants, the presence of the IL-10 ATA/ACC genotype in the recipient has been associated with a moderate risk of GVHD and lower risk of death in remission, 16 more severe GVHD occurring in groups without the IL-10 ATA haplotype.…”
Section: Discussionmentioning
confidence: 99%
“…Since the strongest association was observed in the D1 group, it is conceivable that in the D1, as opposed to the D2 and D3 groups, the recipient signal threshold, affected by heparanase, is higher compared with that of their donors. This delicate balance may be further modulated by the recipient and donor inflammatory cytokine polymorphism, [10][11][12][13][14][15][16] and may lead to hyperactivation of donor T cells and thereby elevate the risk of acute GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Previous studies have implicated polymorphisms in cytokine genes as factors affecting GVHD and survival. [10][11][12][13][14][15][16] Heparanase is the predominant endoglycosidase responsible for heparan sulfate (HS) degradation and the associated release of HS-bound cytokines, chemokines, and bioactive angiogenic-and growth-promoting factors. Heparanase may therefore play an important role in the pathogenesis of GVHD.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In this regard, single nucleotide polymorphisms (SNP) of the genes for cytokines/chemokines and their receptors, minor histocompatibility Ag, genes for innate immunity and those associated with the metabolism of drugs have recently been studied for their possible association with aHSCT outcome, often with controversial results. [4][5][6] Of non-HLA factors, cytokines are important candidates in searching for marker of GVHD. IL-6 is an important proinflammatory cytokine implicated in immune-mediated complications of aHSCT, especially GVHD.…”
Section: Introductionmentioning
confidence: 99%